The Role of Renewable Energy Supply and Carbon Tax in the Improvement of Energy Security: A Case Study of Pakistan (The Pakistan Development Review, 2014)
As energy is a vital element for sustained economic growth and development, therefore energy consumption is used as a basic indicator of people’s living standards. Due to technological and industrial development, the demand of energy in Pakistan is increasing more than the total primary energy supply; therefore, it is confronting the severe energy deficit today. So there should be a serious concern for the government about the energy security and should take actions for the development of indigenous alternative and renewable energy resources. Renewable portfolio supply (RPS), and carbon tax are the two indirect policy options used for the improvement of energy security. Renewable Energy Promotion is used to reduce greenhouse gas emission, promote local energy sources and improve energy security through reducing energy dependency and diversification of energy sources. Carbon tax is an indirect policy option for energy security enhancement through emission reduction. Imposing tax on carbon emission will alter the primary energy supply mix, more efficient fuel and technologies will be substituted for less efficient fuel and technologies. This will reduce the primary energy demand and lead to improved energy security.